Secrets at the Last House Before the Sea - Eeles, Liz (BOOKOUTURE, 2021)
From the attic of Driftwood House there are stunning views of the deep green sea and sapphire sky. But Rosie can't tear her eyes away from the faded photograph in her hands, and the words written on the back that will change everything...